Severe hip joint motion restriction in a patient with diffuse idiopathic skeletal hyperostosis: A case report. Issue 18 (May 2018) - Lee, Wonho; Kim, Wook Ro; Chang, Min Cheol
Abstract: Rationale: Severe limitation of motion (LOM) in the spine occasionally occurs in patients with diffuse idiopathic skeletal hyperostosis (DISH). However, in extraspinal areas, significant LOM has rarely been reported. In this study, we report a patient with DISH who had severe motion restriction within both hip joints. Patient concerns: A 57-year-old man presented with a 10-year history of LOM of bilateral hip joints. He had gait difficulty due to shortened stride length induced by LOM. Also, he had mild bilateral hip pain [numeric rating scale (NRS): 2]. Diagnoses: Hip joint range of motion was 60.3% of normal. The patient had bridging ossification along the anterolateral borders of 7 contiguous vertebrae (T10 to L4) without the findings of ankylosing spondylitis or degenerative disc disease. In addition, severe hyperostosis was diffusely formed around bilateral hip joints. He was diagnosed with DISH. Interventions: No specific treatment was performed for controlling LOM of bilateral hip joints. Meloxicam 15 mg was administered to the patient for the management of mild bilateral hip pain. Outcomes: At 2-month follow-up visit, the degree of LOM in the bilateral hip joints was not changed. However, the patient's pain severity was reduced from NRS 2 to 1. Lessons: We showed that DISH can cause significant motion restriction due to severe hyperostosis in the bilateral hip joints.